Modeling of steel beam-column connections under dynamic excitation - Sheet, Ikhlas S.; Gunasekaran, Umarani; MacRae, Gregory A. (Journal of Structural Engineering, 2024)
A simple non-linear fiber model considering beam elongation is proposed to represent the behaviour of a steel beam-column connection under cyclic loading. The force-displacement response of the model is shown to compare well with those from an experimental study subjected to a cyclic displacement regime.